Choice of Dental Specialty and Career Inclination among Dental Students in Karachi, Pakistan - Asma Naz, Sajjad Ali Darvesh, Saima Hanif, Mujtaba Hussain Kaim Khani, Atif Jawad, Tauqeer Bibi (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the upcoming choices in dental post-graduation and career inclination among female dental students in Karachi. Study design: Descriptive cross sectional study. Place and duration of study: Bhitai Medical & Dental College and Jinnah Medical & Dental College, Karachi from 1st January 2019 to 30th June 2019. Methodology: A structured questionnaire comprising of 9 questions regarding subject and study was distributed to female dental students. Out of 500 questionnaires distributed, 370 responses were received. Results: The average age of the participants was 22.07±1.91 years. There were 81.8% females and 18.2% males. Most of the participants were studying in final years i.e. 31.2%. Three hundred and thirty six (91.1%) intended to pursue specialization in their career. 65% of the participants felt that they had sufficient specialty exposure and encouragement from their dental school to be able to decide which career pathway to choose. Talent in the field 32.2%, further studying 19% and financial reasons 15.2% were the commonest factors which were most likely to affect the decision on specialization. Specialization is too expensive 31.7% and too time consuming 35.2% were the reasons where participants thought that they would be discouraged to do specialization. Post-graduation from abroad, job in public sectors and working in private dental practice were responded opinion regarding about future career plan selection. Conclusion: Most students had an inclination towards oral and maxillofacial pathology, orthodontics and restorative dentistry. The majority of undergraduate students having no intentions to specialize is that they thought it was too time consuming. Key words: Postgraduate, Dental specialty, Career inclination